ANALISIS PENGGUNAAN APLIKASI WAYGROUND TERHADAP MOTIVASI MAHASISWA PGSD PADA EVALUASI PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN - Wigati, Fitria; Sugiyanto, Roso; Salabi, Ahmad Ma'ruf Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the use of the Wayground application as an interactive learning medium and its impact on the motivation of Primary School Teacher Education (PGSD) students in Civic Education assessment activities. The study employed a qualitative research method using observation and interviews as data collection techniques. The findings indicate that Wayground plays a significant role in enhancing students' motivation through its gamification features, immediate feedback, and ease of access. Furthermore, students demonstrated improved assessment outcomes in Civic Education learning. This digital platform can be implemented at various stages of the learning process, including the introduction or apperception stage, core learning activities, and evaluation. It is also relevant for use in different learning models, such as online, offline, and blended learning environments.